CSIG-21. 5-ALA PDT AND TARGETING MEK/ERK SIGNALING ELICITS SYNERGISTIC ANTITUMOR EFFECTS IN DIFFUSE MIDLINE GLIOMA. (12th November 2021) - Price, Gabrielle; Rivera, Daniel; Bouras, Alexandros; Hadjipanayis, Constantinos
Abstract: Diffuse midline gliomas (DMGs) are highly invasive, unresectable tumors in children. To date, there is no effective treatment for DMGs. Fractionated radiotherapy (RT), currently the standard of care, has provided limited disease control. Current obstacles to treatment include the blood brain barrier (BBB) that limits systemic drug delivery, tumor therapy resistance, and brainstem infiltration. Given the unmet need for more effective DMG treatments, photodynamic therapy (PDT), with the precursor photosensitizing agent 5-aminolevulinic acid (5-ALA), is an oncologic treatment that holds promise. 5-ALA PDT of tumors occurs by targeting tumor cells that accumulate the 5-ALA metabolite, protoporphyrin IX (PPIX), with 635 nm light to create deadly reactive oxygen species (ROS). We explore the synergism of 5-ALA PDT with the MEK inhibitor, trametinib, since the RAS/MEK signaling pathway regulates tumor cell proliferation and survival and has been shown to therapeutically enhance PDT in select tumor models. We demonstrated that sub-micromolar levels of 5-ALA PDT and nanomolar levels of trametinib successfully decrease cell proliferation and induce apoptosis in multiple DMG cell lines. Cell viability assays revealed that drug response differs based on the histone mutation (H3.1 or H3.3) of the line. Mechanisms of decreased cell survival involves the generation of reactive oxygen species that induces programmed cell death. Through the use of a DMG genetically engineered mouse model, we also found 5-ALA PDT to induce apoptosis in vivo . The synergistic effects of MEK inhibition and 5-ALA PDT in vitro and apoptotic effects of 5-ALA PDT in vivo, highlights the potential therapeutic efficacy of this treatment modality.